2013
DOI: 10.1002/ejoc.201300975
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic 1,3‐Shift Intermediates in the Interconversions of (Thio)carbamoyl Isocyanates and Carbamoyl Iso(thio)cyanates, R2N–CX–NCO ⇌ R2N–CO–NCX, and in Carbamoylketenes R2N–CO–CH=C=O

Abstract: Cyclic zwitterionic intermediates 3 have been located as reactive intermediates in the thermal 1,3‐shifts of dimethylamino and N‐ piperidinyl groups in carbamoyl isocyanates, carbamoyl isothiocyanates and carbamoylketenes at the B3LYP, M06‐2X and MP2 computational levels of theory. The zwitterion formed in the course of the ketene ⇌ ketene rearrangement shows the highest stabilization (by about 3–5 kcal/mol). The interconversions of carbamoyl isocyanates and isothiocyanates should occur readily at or near room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…When these results were compared with data obtained using the popular B3LYP functional and the recent dispersion-corrected ωB97X-D functional, it was found that the (free) energies computed with the recent functionals M06-2X and ωB97X-D are identical within 1 kcal/mol, while B3LYP gives barriers that are higher by as much as 5 kcal/mol (see the Supporting Information for details). This is in line with other related studies in which M06-2X results agree better with high-level data. This leads to the assumption that M06-2X/6-311+G(d,p) is a robust and reliable theoretical level for studying these and related reactive species.…”
Section: Mechanistic Studiessupporting
confidence: 93%
“…When these results were compared with data obtained using the popular B3LYP functional and the recent dispersion-corrected ωB97X-D functional, it was found that the (free) energies computed with the recent functionals M06-2X and ωB97X-D are identical within 1 kcal/mol, while B3LYP gives barriers that are higher by as much as 5 kcal/mol (see the Supporting Information for details). This is in line with other related studies in which M06-2X results agree better with high-level data. This leads to the assumption that M06-2X/6-311+G(d,p) is a robust and reliable theoretical level for studying these and related reactive species.…”
Section: Mechanistic Studiessupporting
confidence: 93%
“…This reaction is initiated by a nucleophilic attack of the imine nitrogen lone pair on the thiocarbonyl carbon, leading to the four-membered cyclic transition state (or intermediate) TS1 (Scheme and Figure ). It is relevant here to mention the related, purely thermal 1,3- C -to- O shifts of benzoyl groups taking place in the rearrangement of 3-benzoyl-4 H- quinoline-4-ones 12 to 4-benzoyl-oxyquinolines 13 with a barrier of 41.5 kcal/mol (A, Scheme and Figure S3, SI) and the 1,3-shifts of amino groups in thioamides ( 14 → 15 , Scheme , B). …”
Section: Resultsmentioning
confidence: 99%